2023
DOI: 10.1186/s12912-023-01466-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mindfulness-based interventions on burnout and self-compassion among critical care nurses caring for patients with COVID-19: a quasi-experimental study

Sahar Younes Othman,
Nagia I. Hassan,
Alaa Mostafa Mohamed

Abstract: Background Workloads in intensive care units (ICUs) have increased and extremely challenging ethical dilemmas were generated by the coronavirus disease 2019 (COVID-19) pandemic. ICU nurses experience high-stress levels and burnout worldwide. Egyptian studies on the effectiveness of mindfulness-based intervention (MBI) among ICU nurses are limited, although MBI has been shown to reduce stress and burnout. Methods This quasi-experimental study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This manifests as heightened diligence and precision in their work, resulting in proactive prevention and avoidance of potentially risky events and ultimately leading to heightened levels of safety behaviours (Partlak et al., 2021). Consequently, self‐efficacy influences safety behaviours through the chain mediation of burnout and work engagement, thus establishing the chain mediation pathway of ‘self‐efficacy → burnout → work engagement → safety behaviours.’ Previous studies have demonstrated that various psychological interventions, such as cognitive behavioural therapy, positive thinking stress reduction therapy (Othman et al., 2023), psychoeducational group intervention (Bailey et al., 2021), emotional release therapy, etc. (Cheng et al., 2023), can effectively reduce nurses' psychological stress and empathy fatigue while improving work engagement, well‐being, and the sense of occupational benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This manifests as heightened diligence and precision in their work, resulting in proactive prevention and avoidance of potentially risky events and ultimately leading to heightened levels of safety behaviours (Partlak et al., 2021). Consequently, self‐efficacy influences safety behaviours through the chain mediation of burnout and work engagement, thus establishing the chain mediation pathway of ‘self‐efficacy → burnout → work engagement → safety behaviours.’ Previous studies have demonstrated that various psychological interventions, such as cognitive behavioural therapy, positive thinking stress reduction therapy (Othman et al., 2023), psychoeducational group intervention (Bailey et al., 2021), emotional release therapy, etc. (Cheng et al., 2023), can effectively reduce nurses' psychological stress and empathy fatigue while improving work engagement, well‐being, and the sense of occupational benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a positive patient safety culture, nurses are better equipped to rectify their work attitudes, diligently fulfil their work duties and exercise improved control over their safety behaviours. Qualitative studies suggest that nursing necessitates a comprehensive intervention program encompassing individual coaching, team interventions, and organizational development processes to cultivate a positive work climate (Othman et al., 2023). As such, this study reminds managers that interventions aimed at reducing burnout and enhancing work engagement can be implemented to improve nurses' safety behaviours.…”
Section: Discussionmentioning
confidence: 99%